Hybrid sol–gel coatings for corrosion protection of galvanized steel in simulated concrete pore solution - Figueira, Rita B. (2016)
The aim of this experimental research was to study the electrochemical behavior of organic– inorganic hybrid (OIH) coatings for corrosion protection of hot-dip galvanized steel (HDGS) in the first instants of immersion in simulated concrete pore solution (SCPS) (pH > 12.5). The electrochemical performance of the OIH coatings was assessed by electrochemical impedance spectroscopy, potentiodynamic polarization curves, macrocell current density, and polarization resistance. The OIH coatings were prepared via the sol–gel method and were deposited on HDGS surfaces by dip-coating using one or three dip steps. The electrochemical results obtained for HDGS samples coated with OIH matrices in SCPS showed higher corrosion resistance than bare HDGS; as the molecular weight (MW) of Jeffamine increased the barrier protection of the coating decreased. The lowest protection efficiency was found for HDGS samples synthesized with oligopolymers with an MW of 2000. Coatings produced with an oligopolymer of 230 MW conferred the highest protection. The surface morphology of the OIH coatings deposited on HDGS surfaces was studied by atomic force microscopy. The results show that the roughness of the OIH films depends on the MW of Jeffamine and on the number of dip-coating steps used. Thermogravimetry results show that the Jeffamine MW affected the thermal properties of the prepared OIH samples. The prepared OIH materials are thermally stable within the range of 20–80 C.